Managing IT in a Downturn. - Mitchell, Stewart (IT Governance Pub., 2008)
Against this backdrop of turbulence, this pocket guide examines what IT executives can do to stretch budget to maintain a useful and reliable network of IT services, and examine where new technologies, free software and licence renegotiation can make budgets work harder. Because all companies are different, the intention is not to recommend specific changes, but to raise the questions and possibilities that will provoke improvements.